Health literacy on childhood immunization among antenatal women and its associated factors in Seremban district, Negeri Sembilan - Mohamad Yusof, Nazatul Yusrina (2017)
Introduction: Immunization is a development process of immune system in the body against infectious diseases by administration of vaccine, toxoid, antibody, or antitoxin. It’s also recognized as a proven tool to prevent infectious diseases. Despite good coverage of immunization globally and nationally, there are still occurrence of vaccine preventable diseases. One of the reason is inadequate health literacy on immunization. Health literacy is an ability of individual to obtain, process and understanding of the basic health information and healthcare system in order to make a good decision of their health and family members. People with low health literacy has been linked to poor health outcome such as higher rate of hospitalization and less frequent used of preventive care such as vaccination.